Big data and the measurement of public organizations' performance and efficiency: The state-of-the-art. (October 2017) - Rogge, Nicky; Agasisti, Tommaso; De Witte, Kristof
The increasing availability of statistical data raises opportunities for 'big' data and learning analytics. Here, we review the academic literature and research relating to the use of big data analytics in the public sector, and its contribution to public organizations' performance and efficiency. We outline the advantages as well as the limitations of using big data in public sector organizations and identify research gaps in recent studies and interesting areas for future research.